2009
DOI: 10.1038/cr.2009.8
|View full text |Cite
|
Sign up to set email alerts
|

The TAK1-JNK cascade is required for IRF3 function in the innate immune response

Abstract: Interferon regulatory factor (IRF)3 is critical for the transcriptional induction of chemokines and cytokines during viral or bacterial invasion. The kinases Tank binding kinase (TBK)1 and Ikappa B kinase (IKK)ε can phosphorylate the C-terminal part of IRF3 and play important roles in IRF3 activation. In this study, we show that another kinase, c-Jun-NH 2 -terminal kinase (JNK), phosphorylates IRF3 on its N-terminal serine 173 residue, and TAK1 can stimulate IRF3 phosphorylation via JNK. JNK specific inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 55 publications
(80 reference statements)
2
56
0
Order By: Relevance
“…It has recently been reported that Tax interferes with the IFN-␣-induced JAK-STAT pathway by competition with STAT2 for CBP/p300 binding (25), suggesting that Tax controls two different IFN signaling pathways. In addition, the TAK1-JNK cascade is required for IRF3 function in macrophages (18). In contrast, the RNAi experiment ruled out JNK and p38 in IRF3 phosphorylation in HuT-102 cells (data not shown).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…It has recently been reported that Tax interferes with the IFN-␣-induced JAK-STAT pathway by competition with STAT2 for CBP/p300 binding (25), suggesting that Tax controls two different IFN signaling pathways. In addition, the TAK1-JNK cascade is required for IRF3 function in macrophages (18). In contrast, the RNAi experiment ruled out JNK and p38 in IRF3 phosphorylation in HuT-102 cells (data not shown).…”
Section: Resultsmentioning
confidence: 74%
“…TAK1 is known as a key kinase leading to NF-B in tumor necrosis factor-␣ and interleukin-1 signaling pathways (14,15); however, it is dispensable in Tax-dependent constitutive NF-B activation (13). TAK1 has been demonstrated to participate in TLR-mediated activation of NF-B (16) but not the TBK1-IRF3/7 pathway (17,18); however, the role of constitutive TAK1 activation in IFN-regulatory signals triggered by HTLV-1 is still largely unknown.…”
mentioning
confidence: 99%
“…These data clearly showed that LO28 has a distinct ability for IFN-␤ induction compared to EGD. Recent reports have shown that IRF3 plays an essential role in the expression of IFN-␤, and TBK1 and JNK contribute to the activation of IRF3 through phosphorylation of IRF3 at the C terminus and N terminus, respectively (39,54). We thus determined whether the activation of these transcription factors is associated with the increased production of IFN-␤ in LO28-infected macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, JNK was shown to be involved in the phosphorylation of IRF3 (Ser 173 ), acting as a positive regulator of IRF3 activation (28). Therefore, we addressed whether IRAK1 and IKKε had a functional role in MAPK activation downstream of TLR3, as assessed by Western blot analysis (Fig.…”
Section: Irak1 and Ikk« Are Involved In Limiting The Activation Of Tamentioning
confidence: 99%